2020
DOI: 10.1155/2020/7314241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alternate Corrosion and Fatigue on Fatigue Crack Growth Characterization of 2024-T4 Aluminum Alloy

Abstract: To investigate the effect of alternate corrosion and fatigue on fatigue crack growth characterization of 2024-T4 aluminum alloy, the pure fatigue test, “corrosion + fatigue” test (commonly known as pre-corrosion fatigue), and the “fatigue + corrosion + fatigue” alternating test of single-sided notched specimen of 2024-T4 aluminum alloy were carried out. The fatigue crack life of alternate corrosion and fatigue is longer than that of the pre-corrosion fatigue when the corrosion time is the same. And the more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In general, the results show that, regardless of the environment, the fatigue crack growth rates are quite similar for both aluminium alloys. On the other hand, it is noticeable that the crack growth rates in specimens of base material (without corrosion) are of magnitude 10 −5 to 10 −3 mm/cycle, while in corroded specimens crack growth rates are mostly of magnitude 10 −4 mm/cycle [10]. Finally, a significant degradation effect of corrosion was observed in the specimens of both aluminium alloys.…”
Section: Fatigue Crack Growth Ratementioning
confidence: 91%
“…In general, the results show that, regardless of the environment, the fatigue crack growth rates are quite similar for both aluminium alloys. On the other hand, it is noticeable that the crack growth rates in specimens of base material (without corrosion) are of magnitude 10 −5 to 10 −3 mm/cycle, while in corroded specimens crack growth rates are mostly of magnitude 10 −4 mm/cycle [10]. Finally, a significant degradation effect of corrosion was observed in the specimens of both aluminium alloys.…”
Section: Fatigue Crack Growth Ratementioning
confidence: 91%
“…Daniel Kovalov et al [185] studied the corrosion fatigue of aluminium alloy 2024-T351 and found the effects of electrochemical potential, NaCl concentration, loading frequency, and temperature. Zhang T et al [186] developed a model considering the corrosion and fatigue cycle effects of aluminium alloy 2024-T4. They used curve fitting techniques to relate the corrosion time and depth of aluminium alloys.…”
Section: Modelling and Predictive Approachesmentioning
confidence: 99%
“…Although various models [185,186,191] are used to analyse the obtained data and predict the life cycle in non-corrosive and corrosive conditions, the current understanding still needs to consider the specific effects of temperature and humidity. Investigating how temperature and humidity interact to affect fracture toughness and FCGR behaviour is critical to ensure aluminium alloy components' reliable and safe performance in coastal environments.…”
Section: Modelling and Predictive Approachesmentioning
confidence: 99%
“…Danyil Kovalov et al [21] explored corrosion fatigue in aluminium alloy 2024-T351, finding influence from electrochemical potential, NaCl concentration, loading frequency, and temperature. Tianyu Zhang et al [22] developed a model accounting for corrosion and fatigue alternation effects on 2024-T4 aluminium alloy.…”
Section: Introductionmentioning
confidence: 99%